DNA methylation markers in obesity, metabolic syndrome, and weight loss. Issue 5 (4th May 2019) - Samblas, Mirian; Milagro, Fermín I.; Martínez, Alfredo
ABSTRACT: The fact that not all individuals exposed to the same environmental risk factors develop obesity supports the hypothesis of the existence of underlying genetic and epigenetic elements. There is suggestive evidence that environmental stimuli, such as dietary pattern, particularly during pregnancy and early life, but also in adult life, can induce changes in DNA methylation predisposing to obesity and related comorbidities. In this context, the DNA methylation marks of each individual have emerged not only as a promising tool for the prediction, screening, diagnosis, and prognosis of obesity and metabolic syndrome features, but also for the improvement of weight loss therapies in the context of precision nutrition. The main objectives in this field are to understand the mechanisms involved in transgenerational epigenetic inheritance, and featuring the nutritional and lifestyle factors implicated in the epigenetic modifications. Likewise, DNA methylation modulation caused by diet and environment may be a target for newer therapeutic strategies concerning the prevention and treatment of metabolic diseases.